2020
DOI: 10.46637/ach.v1i1.11
|View full text |Cite
|
Sign up to set email alerts
|

The Psychological Well-Being and Self-Compassion on Malaysian Teachers of Counseling and Guidance

Abstract: The national development and government initiatives in realizing educational transformation has made the profession of school counseling and guidance teachers facing a challenging and vulnerable role with stress that affects their well-being. The psychological well-being of school counseling and guidance teachers need to be explored and understood to ensure their services in schools are implemented effectively. The study intends to seek contribution of self-compassion to psychological well-being among school c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 36 publications
0
2
0
1
Order By: Relevance
“…Meskipun individu memiliki cara yang berbeda dalam merespons perubahan dan stres yang timbul, baik dalam hal kesehatan fisik, kesehatan mental, pengaturan diri, maupun lingkungan sosial, selfcompassion tetap berperan penting. Penelitian lainnya yang dilakukan oleh Mohamed, Bakar, & Ifdil (2020) dan Renggani & Widiasavitri (2018) juga menunjukkan bahwa selfcompassion memiliki keterkaitan positif dengan kesejahteraan psikologis. Dalam konteks kesejahteraan mental, self-compassion dapat menjadi faktor yang penting dalam membantu guru honorer sekolah dasar untuk mengelola stres dan tekanan dalam pekerjaan mereka serta meningkatkan kualitas pekerjaan mereka.…”
Section: Pendahuluanunclassified
“…Meskipun individu memiliki cara yang berbeda dalam merespons perubahan dan stres yang timbul, baik dalam hal kesehatan fisik, kesehatan mental, pengaturan diri, maupun lingkungan sosial, selfcompassion tetap berperan penting. Penelitian lainnya yang dilakukan oleh Mohamed, Bakar, & Ifdil (2020) dan Renggani & Widiasavitri (2018) juga menunjukkan bahwa selfcompassion memiliki keterkaitan positif dengan kesejahteraan psikologis. Dalam konteks kesejahteraan mental, self-compassion dapat menjadi faktor yang penting dalam membantu guru honorer sekolah dasar untuk mengelola stres dan tekanan dalam pekerjaan mereka serta meningkatkan kualitas pekerjaan mereka.…”
Section: Pendahuluanunclassified
“…The individual's self-compassion is defined based on their responses in a certain situation which can be positive or negative forms. Research about self-compassion has been conducted over the world which focuses on perspectives of education (Bakar & Ifdil, 2020), clinical (Athanasakou et al, 2022), and psychology (Wong, 2021). Most of the previous research examines self-compassion at any level including adolescents (Marshall et al, 2020;Phuoc & Nguyen, 2020) and adults (Phillips, 2019) to enhance the positive impact on life.…”
Section: Introductionmentioning
confidence: 99%
“…Self-compassion was conducted to investigate the perspectives of Malaysian teachers of counseling and guidance (Mahomed et al, 2019), university students and social media disorders (Mohammad et al, 2016), mental health (Kotera & Neary, 2021), and adolescents' happiness and well-being (Khatib et al, 2021). Results from the previous research showed a significant impact on happiness (Ying et al, 2016) and psychological well-being (Bakar & Ifdil, 2020). The demographic perspective also was investigated in previous research.…”
Section: Introductionmentioning
confidence: 99%